Experimental Study on the Effect of Waste Valve Load and the Volume of Air Chamber on the Performance of the Hydraulic Ram Pump (Hydram) to Water the Paddy Field in Pakandangan, Padang Pariaman Regency - Ichlas Nur; Nota Effiandi; Vera Veronica (Jurnal Teknik Mesin, 2021)
This 2019 DIPA Grand’s research designed and fabricated the size of hydraulic ram (hydram) pump utilized in Pakandangan, Padang Pariaman Regency. There is a water source in this area which has not been functioned adequately to irrigate the paddy field of 10 hectares due to the location of the paddy field which is higher than the water source. However, the use of designed hydram pump has no been maximized as the pump’s optimal performance was not determined yet. Therefore, a hydram pump was designed by varying the load of waste valve in the weight of 400 g, 600 g, 800 g, 1,000 g, and 1,200 gr. It was also varied in the volume of the chamber when the pump operated which were 4.86 lt, 5.76 lt, 6.48 lt, 7.29 lt, and 8.1lt. The height (Hd) of the inlet pipe was 1 m, and the lift height (Hs) of the outlet pipe was 5 m. The results obtained from Pump performance increases with increasing cylinder volume. The increase in the load of the exhaust valve volume of the tube remains a significant decrease. Hydram pump performance occurs at a load of 400 g with a tube volume of 8.1 l with an efficiency of 53%